Experiences of Childhood Caregivers and Marital Attachment in Relation to the Strength of Maternal-Fetal Attachment - Suominen, Sohvi (fi=Turun yliopisto|en=University of Turku|, 2017)
Maternal-fetal attachment is currently viewed as the beginning of an attachment relationship between a mother and a child and as such, has many implications for the child development. The aim of this study was to evaluate whether the mothers’ experiences of childhood caregivers and the attachment to their current partner would be connected to the strength of maternal-fetal attachment at 34 gestational weeks in first time mothers. The study was conducted as a part of a Finnbrain study in the region of Southwest Finland and consisted of 1113 participants. Standardized questionnaires were used to study participants’ experiences of maternal-fetal attachment (MFAS), recalled experiences of parental care and control in childhood (PBI) and attachment to their current romantic partner (ECR-R). Multiple regression analysis was used to study if maternal-fetal attachment at 34 weeks could be predicted with romantic attachment avoidance and anxiety and participants’ maternal and paternal care and control in childhood. The findings revealed that romantic attachment avoidance (β=−.276, p<.001) had a significant negative connection with maternal-fetal attachment. In addition, paternal control in childhood (β=.083, p<.05) and paternal care in childhood (β=−.087, p<.001, reflected variable) had a significant positive connection with maternal-fetal attachment. The findings suggest that the romantic attachment style and the mother’s experiences of their own father’s parenting style are meaningful to the strength of maternal-fetal attachment. Therefore, support for both mothers and for the relationship between mothers and their partners is recommended during pregnancy, especially when the mother presents higher levels of avoidant attachment towards her partner. The finding that the mother’s own father’s parenting style is associated with maternal-fetal attachment supports the notion of intergenerational effects of attachment relationships. Therefore, primary support should be focused on early preventative measures.